Penegakan Hukum Terhadap Penyelundupan Manusia yang Melalui Jalur Provinsi Lampung - Bambang Hartono (Law Faculty of Universitas Bandar Lampung, 2012)
Indonesia as one of the world also has a strong potential for the practice of transnational crime. Transnational crime is not only driven by factors that are wide open free trade or the lack of law enforcement in Indonesia. the problem is how law enforcement against human trafficking through Lampung province? Law enforcement against perpetrators of human trafficking through the Lampung province by the Immigration and other agencies joined in the criminal justice system by doing activities such as: Preemptive, preventive, Repressive